Ileal endogenous amino acid flow of broiler chickens under high ambient temperature. - Soleimani, A. F.; Kasim, Azhar; Alimon, Abdul Razak; Meimandipour, A.; Idrus, Zulkifli (2010)
High environmental temperature has detrimental effects on the gastrointestinal tract of poultry. An experiment was conducted to determine the effect of acute heat stress on endogenous amino acid (EAA) ﬂow in broiler chickens. A total of 90, day-old broiler chicks were housed in battery cages in an environmentally controlled chamber. Chicks were fed a nitrogen-free diet on day 42 following either no heat exposure (no-heat) or 2 weeks exposure to 35 ± 1 C for 3 h from days 28 to 42 (2-week heat) or 1 week exposure to 35 ± 1 C for 3 h from days 35 to 42 (1 week heat). The most abundant amino acid in the ileal ﬂow was glutamic acid, followed by aspartic acid, serine and threonine in nonheat stressed group. The EAA ﬂow in 1-week heat and 2-week heat birds were signiﬁcantly (p < 0.05) higher than those under no heat exposure (14682, 11161 and 9597 mg/kg of dry matter intake respectively). Moreover, the EAA ﬂow of 2-week heat group was less than 1-week heat group by approximately 36%. These observations suggest that the effect of heat stress on EAA ﬂow is mostly quantitative; however, heat stress may also alter the content of EAA ﬂow qualitatively.